Synthesis and Characterization of Series of Methoxy-Substituted Salamo-Type Compounds Having More Flexible O-Alkyl Chain - Dong1, Xiu-Yan; Gao2, Su-Xia; Zhang1, Yu-Jie; Zhang1, Yang; Wang1, Li (Asian Journal of Chemistry, 2014)
Several novel methoxy-substituted Salamo-type compounds have been synthesized by the condensation reactions of 3-methoxy-2-hydroxy-benzaldehyde with 1,7-bis(aminooxy)heptane, 1,8-bis(aminooxy)octane, 1,9-bis(aminooxy)nonane or 1,10-bis(aminooxy)decane in ethanol medium, respectively and characterized by elemental analyses, IR, UV-visible and 1H NMR spectra.